SUBSTANTIATION OF INDICATORS FOR ASSESSING THE EFFECTIVENESS OF MEDICAL CHECK-UPS AMONG SERVICEMEN OF THE REPUBLIC OF UZBEKISTAN - Mirrakhimova Saida Shukhratovna; Prof. Muhammedova Muyassar Gafurdjanovna; Shoira Kakhramonovna Abdusattarova; PhD Ganiev Bakhtiyor Sobirjonovich (Scholar Express Journals, 2024)
In modern conditions, health care of military personnel plays a key role in ensuring national security. In this context, medical examination becomes an important tool for maintaining a high level of physical and mental health of servicemen. The article will consider the justification of indicators for assessing the effectiveness of medical examination of servicepersons of the Republic of Uzbekistan
Keywords: prevention; Health; medicine; dispenserisation